2022
DOI: 10.1111/cdev.13876
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways of integration: Acculturative change and associations with school adjustment in immigrant‐origin adolescents

Abstract: Tracing developmental pathways of immigrant-origin adolescents, this 3-year longitudinal study (2012)(2013)(2014)(2015) examined within-person changes in cultural orientations and their consequences for school adjustment. Multivariate latent growth mixture modeling confirmed multiple pathways of integration, revealing variable acculturative changes along dual trajectories of heritage and mainstream orientations among European-origin (N = 592, M age = 14.45, 55.1% boys) and Turkish-and Moroccan-origin adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…More closely related to the present study, a meta-analysis revealed that adolescents with more positive affect towards their ethnic origin showed better school adjustment, such as higher academic achievement and more favorable attitudes towards school (Rivas-Drake et al 2014). Moreover, minority adolescents who combined cultural identities reported more school belonging and engagement-as related school adjustment indicators (Hillekens et al, 2023). These findings suggest that identity commitments may benefit minority adolescents' school value as well.…”
Section: Identity Commitments and School Valuesupporting
confidence: 80%
See 1 more Smart Citation
“…More closely related to the present study, a meta-analysis revealed that adolescents with more positive affect towards their ethnic origin showed better school adjustment, such as higher academic achievement and more favorable attitudes towards school (Rivas-Drake et al 2014). Moreover, minority adolescents who combined cultural identities reported more school belonging and engagement-as related school adjustment indicators (Hillekens et al, 2023). These findings suggest that identity commitments may benefit minority adolescents' school value as well.…”
Section: Identity Commitments and School Valuesupporting
confidence: 80%
“…Identity development is differentially affected due to different intergroup experiences. For example, combining ethnic and national identities is harder for adolescents from more stigmatized and racialized groups, with important implications for their school adjustment (Hillekens et al, 2023). Similarly, first generation minority youth generally attach more value to their ethnic identity compared to second and later generation peers (Birman & Trickett, 2001).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Scholars have taken great interest in the issue of identity formation among YMBs and in the difficulties they face in their integration process into European societies (Crul, Schneider, & Lelie, 2012; Hillekens, Baysu, & Phalet, 2023; Phalet, Fleischmann, & Hillekens, 2018). Studies adopting Berry's fourfold acculturation model (Berry, 1997) report that integration/biculturalism is the acculturation strategy that leads to higher levels of adaptation compared to separation, assimilation, and marginalization strategies (e.g., Hong et al, 2016; Nguyen & Benet‐Martínez, 2012; Schwartz, Birman, Benet‐Martínez, & Unger, 2017).…”
Section: Introductionmentioning
confidence: 99%